In-situ solid electrolyte for high-pressure system and secondary lithium battery
By using polyfluoropolymer solid electrolyte in secondary lithium batteries, the problem of poor compatibility between electrolyte and metal negative electrode under high-voltage system is solved, the cycle stability and safety of the battery are improved, and more efficient ion migration is achieved.
Patent Information
- Application Number
- CN202411346282.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
The solid electrolyte used in secondary lithium batteries under high-voltage systems is difficult to be compatible with metal negative electrodes, resulting in unevenness of the SEI layer and an increase in impedance, which affects the cycle stability and safety of the battery.
The polyfluoropolymer solid electrolyte formed by polymeric monomer and crosslinking agent in the electrolyte is used to form a polymer frame with strong coverage of the electrolyte by copolymerizing the polyfluoromonomer and the multifunctional monomer to form a polymer frame with strong coverage of the electrolyte, reducing the initiation. The dose of agent is used and improves the uniformity and interface stability of the electrolyte.
The electrolyte compatible with metal lithium under a high-voltage system is realized, which reduces the risk of rupture of the SEI layer, improves the cycling stability and ion migration efficiency of the battery, and enhances the safety and energy density of the battery.
Smart Images

Figure BDA0005063140100000031 
Figure BDA0005063140100000032 
Figure BDA0005063140100000041
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to an in-situ solid electrolyte and a secondary lithium battery for a high-voltage system. Background Art
[0002] In recent years, secondary batteries have developed rapidly and gradually dominated the fields of energy storage, power, 3C, etc. Lithium secondary batteries have the advantages of high energy density, low self-discharge, and long cycle life, while sodium secondary batteries have the advantages of low cost, wide temperature operating range, and high thermal runaway temperature. The current development direction of lithium and sodium secondary batteries tends to be higher energy density and higher safety. In response to this requirement, the development of solid-state and semi-solid-state batteries has become a feasible method. With the continuous deepening of research and gradual industrial application, solid-state batteries still expose some problems. Due to the pursuit of higher energy density, all-solid-state batteries often need to be used in high-voltage systems, and the use of metal negative electrodes leads to further increase in safety requirements. How to design an electrolyte that can be used in high-voltage systems and is compatible with metal negative electrodes is an important part of the current development of secondary batteries.
[0003] In traditional liquid electrolyte systems, in order to cope with high voltage systems, it is often necessary to use a large amount of fluorinated additives or directly use fluorinated solvents, the more typical ones are FEC, FEMC, etc. This type of fluorinated additive has a higher reduction potential and oxidation potential due to its lower LUMO and HOMO energy levels. It can not only preferentially decompose at the negative electrode to form SEI, but also has strong antioxidant ability. However, when the negative electrode is a metal negative electrode, the volume expansion of the negative electrode will be aggravated during charging and discharging, which will cause the formed SEI to be repeatedly destroyed, and in the long run, the SEI thickness will be too large and uneven, which greatly affects the impedance, cycle stability and safety of the secondary battery.
[0004] A Chinese patent with publication number CN115133222A discloses a method for coating the front and back sides of a diaphragm, comprising the following steps: Step 1: using a ceramic base film, a PE base film, a polypropylene / polyethylene / polypropylene multilayer base film, a glass fiber base film, etc. as a basic diaphragm; Step 2: selecting a high molecular polymer with a molecular weight of 50,000 to 3 million as a binder, mixing the binder and the functional material evenly, and the mass ratio of the polymer binder to the functional material is 1:2 to 20; Step 3: coating the base film on the positive electrode side, and the functional material used for coating is a hygroscopic material, that is, a porous material that can store water molecules; Step 4: coating the base film on the negative electrode side, and the functional material used for coating is an inorganic substance that can react chemically and alloy with lithium, and finally a double-sided coated composite diaphragm is obtained. The Chinese patent application number CN201980098870.8 discloses a method for preparing an in-situ solid polymer electrolyte based on polyvinylidene fluoride hexafluoropropylene, comprising the following steps: step 1, dissolving 2.478g of polyvinylidene fluoride hexafluoropropylene in 20mL of N,N-dimethylformamide, stirring and mixing evenly to obtain a mixed solution A; step 2, using the mixed solution A obtained in step 1 as an electrospinning solution, and using an electrospinning method to obtain a polymer diaphragm matrix, the electrospinning voltage is 20kV, the rotation speed is 250rpm, the distance between the emitter and the receiving substrate is 10cm, and the flow rate is 5mL / h; step 3, the mixed solution A obtained in step 2 is used as an electrospinning solution, and the electrospinning voltage is 20kV, the rotation speed is 250rpm, the distance between the emitter and the receiving substrate is 10cm, and the flow rate is 5mL / h. The polymer membrane matrix is placed in a vacuum drying oven at 70°C for drying; step 4, in a glove box, under a nitrogen environment, 0.28g of neopentyl glycol diacrylate, 0.12g of vinyl ethylene carbonate, 0.561g of lithium bis(fluorosulfonyl)imide, 0.002g of azobisisobutyronitrile and 4g of a commercial electrolyte are mixed to obtain a mixed solution B, and magnetic stirring is performed for 2h; step 5, the polymer membrane obtained in step 3 is placed in a battery shell with an electrode assembly, and then 40μL of the mixed solution B obtained in step 4 is added dropwise, and the battery is sealed and left to stand for 6h; step 6, the battery obtained in step 5 is placed in an oven at 60°C for 12h; and finally the electrolyte is obtained.
[0005] However, the modification method described in the above scheme is accompanied by the risk of membrane coating peeling, increasing battery internal resistance, and destroying the high-nickel ternary positive electrode structure. Although the use of acrylic acid ester and carbonate monomers can ensure a wider electrochemical window and help the metal lithium to deposit more evenly, it will also lead to an increase in internal resistance, especially affecting the migration of lithium ions on the positive electrode side. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide an in-situ solid electrolyte and a secondary lithium battery for a high-voltage system, wherein the in-situ solid electrolyte has a controllable degree of polymerization, good compatibility with the positive electrode and strong interface stability.
[0007] The present invention provides an in-situ solid electrolyte for a high-voltage system, which is formed by polymerization of monomers and a cross-linking agent in an electrolyte;
[0008] The polymerizable monomers include a first monomer and a second monomer;
[0009] The first monomer is as shown in formula (I) and / or formula (II); the second monomer is selected from acrylate monomers and / or amide monomers;
[0010]
[0011] Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles;
[0012] n1 and n2 are each independently selected from integers of 1 to 5;
[0013] R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group;
[0014] R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group;
[0015] The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group;
[0016] The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group;
[0017] R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
[0018] Preferably, A in the formula (I) and the formula (II) is independently selected from one of the formulas (1) to (6):
[0019]
[0020] Preferably, R is selected from one of the structures shown in formula (7) to formula (13):
[0021]
[0022] The R1 and R2 are each independently selected from the structure shown in formula (14) or formula (15):
[0023]
[0024] Preferably, the second monomer is selected from one or more of isobornyl methacrylate, isobornyl acrylate, N,N'-methylenebisacrylamide, methacrylamide, N-isopropylacrylamide, N-(3-dimethylaminopropyl)methacrylamide, N-vinylcaprolactam, methacrylamide, methacrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate and n-butyl acrylate;
[0025] The crosslinking agent is selected from one or more of neopentyl glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, hexanediol diacrylate, di(trimethylolpropane tetraacrylate), pentaerythritol triacrylate, divinyl ether, trimethylolpropane triglycidyl ether, trivinyl cyanurate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate and diallyl sulfide.
[0026] Preferably, the molar ratio of the polymerizable monomer to the crosslinking agent is (5-15):1;
[0027] The molar ratio of the first monomer to the second monomer is (5-9):(5-1);
[0028] The total mass of the polymerized monomer and the cross-linking agent is 1% to 10% of the mass of the in-situ solid electrolyte.
[0029] Preferably, the electrolyte comprises an organic solvent, a lithium salt and an additive;
[0030] The organic solvent includes a carbonate solvent;
[0031] The concentration of the lithium salt in the electrolyte is 0.5 to 2 mol / L;
[0032] The additive is selected from one or more of sulfonate compounds, sulfate compounds, fluorinated carbonate compounds, unsaturated cyclic carbonate compounds, borate compounds, trimethylsilyl ester compounds, nitrile compounds and fluorine-containing lithium salt compounds; the mass of the additive is 0.1% to 6% of the mass of the electrolyte.
[0033] The present invention also provides a method for preparing an in-situ solid electrolyte for a high-voltage system, comprising the following steps:
[0034] The polymerization monomer and the cross-linking agent are added to the electrolyte, and then the initiator is added in an amount of 0.1wt% to 1wt% of the polymerization monomer. After the reaction is continued, an in-situ solid electrolyte is obtained;
[0035] The polymerizable monomers include a first monomer and a second monomer;
[0036] The first monomer is as shown in formula (I) and / or formula (II); the second monomer is selected from acrylate monomers and / or amide monomers;
[0037]
[0038] Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles;
[0039] n1 to n3 are each independently selected from integers of 1 to 5;
[0040] R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group;
[0041] R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group;
[0042] The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group;
[0043] The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group;
[0044] R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
[0045] The present invention also provides a lithium ion battery, comprising the above-mentioned in-situ solid electrolyte for high-voltage system.
[0046] The present invention also provides a polyfluoro polymer monomer, as shown in formula (I) or formula (II):
[0047]
[0048] Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles;
[0049] n1 to n3 are each independently selected from integers of 1 to 5;
[0050] R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group;
[0051] R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group;
[0052] The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group;
[0053] The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group;
[0054] R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
[0055] The present invention also provides a method for preparing a polyfluoro polymer monomer, comprising the following steps:
[0056] In a protective atmosphere, the compound represented by formula (III) and the compound represented by formula (IV) or formula (V) are mixed in an organic solvent and reacted under low temperature conditions to obtain a polyfluoro polymer monomer;
[0057] R-OH formula (IV);
[0058] A is selected from a substituted or unsubstituted oxygen-containing heterocycle;
[0059] n1 and n2 are each independently selected from integers of 1 to 5;
[0060] R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group;
[0061] R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group;
[0062] The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group;
[0063] The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group;
[0064] R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
[0065] The present invention provides an in-situ solid electrolyte for a high-voltage system, which is formed by initiating polymerization of monomers and crosslinking agents in an electrolyte; the polymerization monomers include a first monomer and a second monomer; the first monomer is as shown in formula (I) and / or formula (II); the second monomer is selected from acrylate monomers and / or amide monomers. Compared with the prior art, the in-situ solid electrolyte provided by the present invention has the following specific advantages:
[0066] 1) The substituent contains a polyfluorinated group, which is an electron-withdrawing group with a low LUMO energy level. It is easy to promote the polymerization of the electron-donating group C=C when the battery is powered on. It is an effective electropolymerization monomer and can greatly reduce the amount of initiator used;
[0067] 2) Compared with traditional thermally initiated free radical polymerization monomers, electropolymerized monomers have better polymerization uniformity, and residual monomers can act as film-forming additives, which is beneficial to the long cycle of batteries;
[0068] 3) The present invention copolymerizes a polyfluorinated monomer with a multifunctional monomer, and while a portion of the vinyl groups are used as the main chain for addition polymerization, the remaining vinyl groups can be used as cross-linking functional groups, and can be cross-linked and polymerized with other monomers to form a polymer framework with strong electrolyte coating properties, which is beneficial to stabilizing the interface, slowing down the rupture of the LiF layer caused by the volume change of metallic lithium and the uneven thickness of the SEI layer during long-term cycles;
[0069] 4) There is a small amount of residual alkali on the surface of the solid electrolyte added on the positive electrode side, and a small amount of hydroxyl groups in it can promote the electropolymerization of fluorinated monomers;
[0070] 5) The substituent is an oxygen-containing hydrofluoroether. Compared with the traditional perfluoroalkyl group, the polymer chain segment is more sensitive to Li + The transport efficiency is higher, resulting in a higher ion transfer number in the overall electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This is the XPS spectrum of the negative electrode of the lithium battery in Example 1 of the present invention;
[0072] Figure 2 This is the XPS spectrum of the negative electrode of the lithium battery in Example 2 of the present invention;
[0073] Figure 3 This is the XPS spectrum of the negative electrode of the lithium battery in Example 3 of the present invention;
[0074] Figure 4 This is the XPS spectrum of the negative electrode of the lithium battery in Example 4 of the present invention;
[0075] Figure 5 This is the XPS spectrum of the negative electrode of the lithium battery in Example 5 of the present invention;
[0076] Figure 6This is the XPS spectrum of the negative electrode of the lithium battery in Example 6 of the present invention;
[0077] Figure 7 This is the XPS spectrum of the negative electrode of the lithium battery in Example 7 of the present invention;
[0078] Figure 8 This is the XPS spectrum of the negative electrode of the lithium battery in Comparative Example 1 of the present invention;
[0079] Fig. 9 This is the XPS spectrum of the negative electrode of the lithium battery in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0080] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0081] The present invention provides a polyfluoro polymer monomer, as shown in formula (I) or formula (II):
[0082]
[0083] Wherein, A in formula (I) and formula (II) is independently a substituted or unsubstituted oxygen-containing heterocycle, preferably a substituted or unsubstituted five-membered nitrogen-containing heterocycle, a substituted or unsubstituted six-membered nitrogen-containing heterocycle; the number of oxygen atoms in the nitrogen-containing heterocycle is preferably 1 to 3, specifically 1, 2 or 3; the substituent in the substituted nitrogen-containing heterocycle is preferably a C1 to C5 alkyl group and / or a C1 to C5 perfluoroalkyl group, more preferably a C1 to C3 alkyl group and / or a C1 to C3 perfluoroalkyl group, and even more preferably a C1 to C2 alkyl group and / or a C1 to C2 perfluoroalkyl group; in the present invention, one of formulas (1) to (6) is most preferred:
[0084]
[0085] n1 to n3 are each independently an integer of 1 to 5, preferably an integer of 1 to 4, more preferably an integer of 1 to 3, and even more preferably 1 or 2.
[0086] R is a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group, preferably a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C15 alkenyl group, more preferably a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C10 alkenyl group, further preferably a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C8 alkenyl group, further preferably a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C The C6 alkenyl is most preferably a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C4 alkenyl; the number of double bonds in the unsaturated carbocyclic ring containing a carbon-carbon double bond is preferably 1-2, more preferably 1; the number of double bonds in the alkenyl is preferably 1-2, more preferably 1; the substituent in the substituted C2-C20 alkenyl is preferably a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group and a C1-C5 perfluoroalkyl group. One or more of, more preferably one or more of substituted or unsubstituted unsaturated carbocyclic ring containing carbon-carbon double bonds, C1-C3 alkyl groups and C1-C3 perfluoroalkyl groups, and more preferably one or more of substituted or unsubstituted unsaturated carbocyclic ring containing carbon-carbon double bonds, C1-C2 alkyl groups and C1-C2 perfluoroalkyl groups; the substituted or unsubstituted unsaturated carbocyclic ring containing carbon-carbon double bonds is preferably a substituted or unsubstituted unsaturated four-membered carbocyclic ring containing carbon-carbon double bonds, a substituted or unsubstituted unsaturated five-membered carbocyclic ring containing carbon-carbon double bonds, or a substituted or unsubstituted unsaturated six-membered carbocyclic ring containing carbon-carbon double bonds; the substituent in the substituted unsaturated carbocyclic ring containing carbon-carbon double bonds is preferably a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group, more preferably a C1-C3 alkyl group and / or a C1-C3 perfluoroalkyl group, and more preferably a C1-C2 alkyl group and / or a C1-C2 perfluoroalkyl group; and R contains a perfluoroalkyl group.
[0087] In a specific embodiment provided by the present invention, R is one of the structures shown in formula (7) to formula (13):
[0088]
[0089] R1 and R2 are each independently a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group, preferably a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C15 alkenyl group or a C1-C8 perfluoroalkyl group, more preferably a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C10 alkenyl group or a C1-C5 perfluoroalkyl group, and still more preferably a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C8 alkenyl group or a C1-C5 perfluoroalkyl group. Preferably, the number of double bonds in the unsaturated carbocyclic ring containing carbon-carbon double bonds is 1 to 2, more preferably 1; the number of double bonds in the alkenyl group is preferably 1 to 2, more preferably 1; the substituents in the substituted C2 to C20 alkenyl group are preferably The substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, or a C1-C5 perfluoroalkyl group, more preferably a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C3 alkyl group, or a C1-C3 perfluoroalkyl group, and more preferably a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C2 alkyl group, or a C1-C2 perfluoroalkyl group; the substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond is preferably a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond. An unsaturated four-membered carbocyclic ring containing a carbon-carbon double bond, a substituted or unsubstituted unsaturated five-membered carbocyclic ring containing a carbon-carbon double bond, or a substituted or unsubstituted unsaturated six-membered carbocyclic ring containing a carbon-carbon double bond; the substituent in the substituted unsaturated carbocyclic ring containing a carbon-carbon double bond is preferably a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group, more preferably a C1-C3 alkyl group and / or a C1-C3 perfluoroalkyl group, and even more preferably a C1-C2 alkyl group and / or a C1-C2 perfluoroalkyl group; and at least one of R1 and R2 contains a perfluoroalkyl group and at least one contains a carbon-carbon double bond.
[0090] In a specific embodiment provided by the present invention, R1 and R2 are each independently a structure represented by formula (14) or formula (15):
[0091]
[0092] In a specific embodiment provided by the present invention, the polyfluoro polymer monomer is one or more of the structures shown in formula (I-1) to formula (I-7):
[0093]
[0094] The present invention also provides a method for preparing a polyfluoro polymer monomer, comprising the following steps: in a protective atmosphere, mixing a compound represented by formula (III) with a compound represented by formula (IV) or formula (V) in an organic solvent, and reacting them under low temperature conditions to obtain a polyfluoro polymer monomer;
[0095] R-OH formula (IV);
[0096] A is a substituted or unsubstituted oxygen-containing heterocycle; n1 and n2 are each independently an integer of 1 to 5; R is a substituted unsaturated carbocycle containing a carbon-carbon double bond or a substituted C2-C20 alkenyl; R1 and R2 are each independently a substituted or unsubstituted unsaturated carbocycle containing a carbon-carbon double bond, a substituted C2-C20 alkenyl or a C1-C10 perfluoroalkyl; the substituent in the substituted C2-C20 alkenyl is selected from one or more of a substituted or unsubstituted unsaturated carbocycle containing a carbon-carbon double bond, a C1-C5 alkyl and a C1-C5 perfluoroalkyl; the substituent in the substituted unsaturated carbocycle containing a carbon-carbon double bond is selected from a C1-C5 alkyl and / or a C1-C5 perfluoroalkyl; and R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one contains a carbon-carbon double bond.
[0097] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used. The A, n1, n2, R, R1 and R2 are the same as those described above and will not be elaborated herein.
[0098] In a specific embodiment provided by the present invention, the compound represented by formula (III) is preferably prepared according to the following method: the amino ether represented by formula (V) and trichloromethyl carbonate (BTC) are heated in an organic solvent to react to obtain the compound represented by formula (III); the mass ratio of the amino ether represented by formula (V) to BTC is preferably (40-90): (50-100), more preferably (40-80): (50-90), further preferably (40-60): (50-80), and most preferably 50: (50-60); the organic solvent is an organic solvent well known to those skilled in the art, and there is no special limitation. In the present invention, dichloromethane, tetrahydrofuran, N,N-dimethylformamide (DMF) and N-methylpyrrolidone are preferably used. one or more of pyrrolidones; the temperature of the heating reaction is preferably 70°C to 90°C, more preferably 75°C to 85°C, and more preferably 80°C; the time of the heating reaction is preferably 4 to 8h, and more preferably 5 to 6h; the heating reaction is preferably carried out under stirring; the stirring speed is preferably 300 to 600rpm, more preferably 300 to 500rpm, and more preferably 300 to 400rpm; after the heating reaction is completed, it is preferably dried to obtain a compound represented by formula (III); the drying is preferably vacuum drying; the drying temperature is preferably 80°C to 100°C, more preferably 85°C to 95°C, and more preferably 90°C; the drying time is preferably 8 to 12h, more preferably 9 to 11h, and more preferably 10h.
[0099]
[0100] In a specific embodiment provided by the present invention, the compound represented by formula (III) can be specifically 2-(isocyanomethyl)-1,4-dioxane.
[0101] In a specific embodiment provided by the present invention, the compound represented by formula (IV) or formula (V) can be specifically 1-(trifluoromethyl)cyclopent-2-ene-1-ol, 1-(trifluoromethyl)cyclohex-2-ene-1-ol, 1-(perfluoroethyl)cyclohex-2-ene-1-ol, (E)-1,1,1-trifluoro-2-(trifluoromethyl)-6-(2,6,6-trimethylcyclohex-1-ene-1-yl)hexyl -5-ene-2,4-diol, 1,1,1-trifluoro-2-(trifluoromethyl)but-3-ene-2-ol, 1,1,1-trifluoropent-4-ene-2-ol, 4,4,5,5,5-pentafluoro-3-methylpent-1-ene-3-yl and 1,1,1,2,2-pentafluoro-3-(perfluoropropane-2-yl)hexyl-5-ene-3-ol, preferably 1-(trifluoromethyl)cyclohex-2-ene-1-ol.
[0102] In a protective atmosphere, the compound represented by formula (III) and the compound represented by formula (IV) or formula (V) are mixed in an organic solvent and reacted under low temperature conditions; the protective atmosphere can be any protective atmosphere well known to those skilled in the art and is not particularly limited. In the present invention, nitrogen is preferably used; the mass ratio of the compound represented by formula (III) to the compound represented by formula (IV) or formula (V) is preferably (50-75):(60-90), more preferably (50-70):(60-80), and more preferably (50-60):(60-80); the ratio of the compound represented by formula (III) to the organic solvent is preferably (50-75) g:(400-900) mL, more preferably (50-70) g:(400-800) mL, and more preferably (50-60) g:(400-600) mL; the organic solvent can be any organic solvent well known to those skilled in the art and is not particularly limited. In the present invention, dichloromethane, N,N-dimethylformamide are preferably used. (DMF), tetrahydrofuran (THF) and acetonitrile; in the present invention, it is preferred to first mix the compound represented by formula (III) with the organic solvent under low temperature conditions, and then add the compound represented by formula (IV) or formula (V) to react under low temperature conditions; the temperature of the low temperature conditions is preferably lower than 10°C; the mixing of the compound represented by formula (III) with the organic solvent under low temperature conditions is preferably carried out under stirring conditions; the stirring speed is preferably 300-650rpm, more preferably 300-500rpm; the mixing time of the compound represented by formula (III) with the organic solvent under low temperature conditions is preferably 2-5h, more preferably 2-4h, and more preferably 2-3h; the reaction temperature is preferably lower than 10°C; the reaction is preferably carried out under stirring conditions; the stirring speed is preferably 300-650rpm, more preferably 300-500rpm; the reaction time is preferably 10-14h, more preferably 10-12h.
[0103] After the reaction is completed, it is preferably washed in an alkaline solution, dried after adding a desiccant, and then recrystallized to obtain a polyfluoropolymer monomer; the alkaline solution can be an alkaline solution well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably an alkali metal hydroxide solution, and more preferably a potassium hydroxide solution and / or a sodium hydroxide solution; the concentration of the alkaline substance in the alkaline solution is preferably 0.05-0.2 mol / L, more preferably 0.08-0.15 mol / L, and more preferably 0.1-0.12 mol / L; the desiccant can be an inorganic desiccant well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably anhydrous copper sulfate; the drying time is preferably 8-12 h, more preferably 9-11 h, and more preferably 10 h; the drying is preferably carried out in a vacuum environment; the solvent used for the recrystallization is preferably an ether solvent and / or a chlorinated alkane solvent, and more preferably one or more of petroleum ether, dichloromethane and chloroform.
[0104] The present invention also provides an in-situ solid electrolyte for a high voltage system, which is formed by polymerization of monomers and a cross-linking agent in an electrolyte;
[0105] The polymerizable monomers include a first monomer and a second monomer;
[0106] The first monomer is as shown in formula (I) and / or formula (II); the second monomer is an acrylate monomer and / or an amide monomer;
[0107]
[0108] Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles;
[0109] n1 and n2 are each independently selected from integers of 1 to 5;
[0110] R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group;
[0111] R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group;
[0112] The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group;
[0113] The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group;
[0114] R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
[0115] In the present invention, the first monomer is one or more of the above-mentioned polyfluorinated polymer monomers; A, n1, n2, R, R1 and R2 are the same as described above and will not be repeated here.
[0116] In the present invention, the second monomer is an acrylate monomer and / or an amide monomer; the acrylate monomer can be any acrylate monomer well known to those skilled in the art without any special limitation; the amide monomer can be any amide monomer well known to those skilled in the art without any special limitation; in a specific embodiment provided by the present invention, the second monomer is preferably one or more of isobornyl methacrylate, isobornyl acrylate, N,N'-methylenebisacrylamide, methacrylamide, N-isopropylacrylamide, N-(3-dimethylaminopropyl)methacrylamide, N-vinylcaprolactam, methacrylamide, methacrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate and n-butyl acrylate.
[0117] In the present invention, the cross-linking agent is a cross-linking agent well known to those skilled in the art, and there is no particular limitation. In the present invention, it is preferably a multifunctional monomer, more preferably one or more of (meth)acrylate, vinyl and vinyl ether multifunctional monomers, and further preferably one or more of neopentyl glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, hexanediol diacrylate, di(trimethylolpropane tetraacrylate), pentaerythritol triacrylate, divinyl ether, trimethylolpropane triglycidyl ether, trivinyl cyanurate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate and diallyl sulfide.
[0118] In a specific embodiment provided by the present invention, the molar ratio of the first monomer to the second monomer is preferably (5-9):(5-1), more preferably (6-9):(4-1), further preferably (7-9):(3-1), and most preferably 8:1.
[0119] In a specific embodiment provided by the present invention, the molar ratio of the polymerizable monomer to the cross-linking agent is preferably (5-15):1, more preferably (6-14):1, further preferably (8-12):1, and most preferably (9-10):1.
[0120] According to the present invention, the electrolyte can be any electrolyte well known to those skilled in the art without any special limitation. In a specific embodiment provided by the present invention, the electrolyte includes an organic solvent, a lithium salt and an additive.
[0121] The organic solvent may be any organic solvent known to those skilled in the art without any particular limitation. In the present invention, the organic solvent preferably includes a carbonate solvent; the carbonate solvent preferably includes a cyclic carbonate solvent and / or a chain carbonate solvent, and more preferably includes a cyclic carbonate solvent and a chain carbonate solvent; the mass ratio of the cyclic carbonate solvent to the chain carbonate solvent is preferably (1-4):(9-6), more preferably (2-3):(8-7), and even more preferably 2.5:8.5; the cyclic carbonate solvent is preferably ethylene carbonate (EC) and / or propylene carbonate (PC); the chain carbonate solvent is preferably one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC).
[0122] The lithium salt is a lithium salt well known to those skilled in the art without any special restrictions. In the present invention, it is preferably one or more of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). The concentration of the lithium salt in the electrolyte is preferably 0.5 to 2 mol / L, more preferably 1 to 1.5 mol / L. In a specific embodiment provided by the present invention, the lithium salt preferably includes a first lithium salt and a second lithium salt. The first lithium salt is preferably a fluorine-containing sulfonyl imide lithium salt, more preferably lithium bis(difluorosulfonyl)imide (LiFSI) and / or lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). Lithium methylsulfonylimide (LiTFSI); the second lithium salt is preferably a boron-containing lithium salt, more preferably lithium bis(oxalatoborate) (LiBOB) and / or lithium difluorooxalatoborate (LiDFOB); the concentration of the first lithium salt in the electrolyte is preferably 0.5-1.5 mol / L, more preferably 0.8-1.2 mol / L, more preferably 0.9-1.1 mol / L, and most preferably 1 mol / L; the concentration of the second lithium salt in the electrolyte is preferably 0.05-0.5 mol / L, more preferably 0.05-0.3 mol / L, more preferably 0.05-0.2 mol / L, more preferably 0.08-0.16 mol / L, more preferably 0.1-0.16 mol / L, and most preferably 0.1 mol / L.
[0123] In a specific embodiment provided by the present invention, the electrolyte further includes an additive; the additive is a basic additive well known to those skilled in the art, and is not particularly limited. In the present invention, it is preferably one or more of sulfonate compounds, sulfate compounds, fluorinated carbonate compounds, unsaturated cyclic carbonate compounds, borate compounds, trimethylsilyl ester compounds, nitrile compounds and fluorine-containing lithium salt compounds; the sulfonate compounds are preferably one or more of 1,3-propane sultone, 1,4-butane sultone, methane disulfonic acid methylene ester and 1,3-propylene sultone; the sulfate compounds are preferably one or more of vinyl sulfate (DTD), trimethylene cyclic sulfate, methyl vinyl sulfate, 4,4'-disulfated vinyl ester and propylene sulfite (PS); the fluorinated carbonate compounds Preferably, it is fluoroethylene carbonate (FEC); the unsaturated cyclic carbonate compound is preferably vinylene carbonate (VC) and / or vinyl ethylene carbonate; the borate compound is preferably one or more of trimethyl borate, triethyl borate, tripropyl borate, tributyl borate and triphenyl borate; the trimethylsilyl ester compound is preferably one or more of tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite and tris(trimethylsilyl)trifluoromethanesulfonate; the nitrile compound is preferably one or more of succinonitrile, adiponitrile and 1,3,6-hexanetriconitrile; the fluorine-containing lithium salt compound is preferably lithium difluorophosphate (LiPO2F2); the mass of the additive is preferably 0.1% to 6% of the mass of the electrolyte, more preferably 1% to 6%, and even more preferably 2% to 5.5%.
[0124] In a specific embodiment provided by the present invention, the additive includes a fluorinated carbonate compound and a sulfate compound; the mass of the fluorinated carbonate compound is preferably 1% to 3% of the mass of the electrolyte, more preferably 2% to 3%; the mass of the sulfate compound is preferably 1% to 2.5% of the mass of the electrolyte, more preferably 2% to 2.5%.
[0125] In a specific embodiment provided by the present invention, the sulfate ester compound includes vinyl sulfate (DTD) and propylene sulfite (PS); the mass of the vinyl sulfate (DTD) is preferably 0.5% to 1.5% of the mass of the electrolyte; the mass of the propylene sulfite (PS) is preferably 0.5% to 1% of the mass of the electrolyte.
[0126] In a specific embodiment provided by the present invention, the total mass of the polymerized monomer and the cross-linking agent is preferably 1% to 10% of the mass of the in-situ solid electrolyte, more preferably 2% to 8%, further preferably 4% to 6%, and most preferably 5%.
[0127] The present invention also provides a method for preparing an in-situ solid electrolyte for a high-voltage system, comprising the following steps: adding a polymerizable monomer and a cross-linking agent to an electrolyte, mixing, adding an initiator, and continuing the reaction to obtain an in-situ solid electrolyte;
[0128] The polymerizable monomers include a first monomer and a second monomer;
[0129] The first monomer is as shown in formula (I) and / or formula (II); the second monomer is selected from acrylate monomers and / or amide monomers;
[0130]
[0131] Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles;
[0132] n1 to n3 are each independently selected from integers of 1 to 5;
[0133] R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group;
[0134] R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group;
[0135] The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group;
[0136] The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group;
[0137] R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
[0138] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used; the polymerizable monomers, cross-linking agents and electrolytes are the same as those described above and will not be elaborated herein.
[0139] In the present invention, the electrolyte is preferably prepared according to the following method: an organic solvent is mixed with a lithium salt and stirred for the first time to obtain a mixed solution; the mixed solution is mixed with an additive and stirred for a second time to obtain an electrolyte; the organic solvent is preferably refrigerated at a low temperature and then mixed with the lithium salt; the refrigeration temperature is preferably 0°C to -15°C; the refrigeration time is preferably 2 to 4 hours; the rotation speed of the first stirring is preferably 400 to 1000 rpm; the first stirring time is preferably 2.5 to 6 hours; the rotation speed of the second stirring is preferably 400 to 1000 rpm; the second stirring time is preferably 0.5 to 2 hours.
[0140] The polymerized monomer and the cross-linking agent are added to the electrolyte, and then the initiator is added after mixing. After continuing the reaction, an in-situ solid electrolyte is obtained; the mixing speed is preferably 400-1000rpm, more preferably 500-800rpm, and more preferably 600rpm; the mixing time is preferably 0.5-2h, more preferably 0.8-1.5h, and more preferably 1h; the initiator can be an initiator well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably an azo initiator, and more preferably azobisisobutyronitrile (AIBN); the mass of the initiator is preferably 0.1% to 1% of the mass of the polymerized monomer; the continued reaction is preferably carried out under stirring; the stirring speed is preferably 400-1000rpm, more preferably 500-800rpm, and more preferably 600rpm; the continued reaction time is preferably 1-4h, and more preferably 2-3h.
[0141] The present invention also provides a lithium ion battery, the above-mentioned in-situ solid electrolyte for high-voltage system.
[0142] In a specific embodiment provided by the present invention, the lithium ion battery further comprises a positive electrode, a negative electrode and a separator; the positive electrode preferably comprises a positive electrode active material, a conductive agent, a binder and a solid electrolyte; the positive electrode active material can be an active material well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of lithium nickel cobalt manganese oxide, lithium cobalt oxide and lithium nickel manganese oxide, more preferably NCM811, NCM523, NCM613, 4.53VLCO, 4.6VLCO or LNMO; the conductive agent can be a conductive agent well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably conductive carbon; the solid electrolyte can be a solid electrolyte well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably at least one of NASICO type, antiperovskite type and garnet type; in the embodiment provided by the present invention, NASICO type Li 1.3 Al 0.3 Ti 1.7(PO4)3 is used as an example for explanation; the mass ratio of the positive electrode active material, conductive agent, binder and solid electrolyte is preferably 9.5:0.3-x:0.2:x; x is 0.05-0.2, preferably 0.05-0.15, more preferably 0.08-0.12, and most preferably 0.1; the negative electrode is preferably a lithium metal negative electrode; the diaphragm is any diaphragm well known to those skilled in the art, and there is no special limitation. In the present invention, a polypropylene diaphragm coated with aluminum oxide on one side is preferred.
[0143] The present invention also provides a method for preparing a lithium ion battery, comprising assembling a positive electrode, a negative electrode and a separator into a battery, adding an in-situ solid electrolyte, standing under heating conditions, and then charging for polymerization to obtain a lithium ion battery; the positive electrode, negative electrode, separator, and in-situ solid electrolyte are the same as described above and are not repeated here; the heating temperature is preferably 40°C to 60°C, more preferably 40°C to 50°C, and more preferably 45°C; the standing time is preferably 15 to 30h, more preferably 20 to 28h, and more preferably 24h; the charging rate is preferably 0.1 to 0.3C, more preferably 0.2C; the charging is preferably to 40% SOC to 60% SOC, more preferably to 50% SOC.
[0144] In order to further illustrate the present invention, an in-situ solid electrolyte and a secondary lithium battery for a high-voltage system provided by the present invention are described in detail below in conjunction with embodiments.
[0145] The reagents used in the following examples are all commercially available.
[0146] Example 1
[0147] Synthesis of monomers: 1) 50 g of BTC (trichloromethyl carbonate) and 50 g of amino ether were dissolved in DMF, heated to 80° C., and stirred at 300 rpm for 5 h to obtain a mixture 1.
[0148] The mixture 1 was placed in a vacuum oven at 90° C. and allowed to stand for 10 h to obtain 2-(isocyanomethyl)-1,4-dioxane.
[0149]
[0150] 2) Add 50 g of 2-(isocyanomethyl)-1,4-dioxane to 400 mL of dichloromethane, stir at 300 rpm for 2 h under a nitrogen environment, and use a water cooling device to ensure that the solvent temperature is lower than 10° C. during synthesis to obtain a mixed solution, then add 60 g of 1-(trifluoromethyl)cyclohex-2-en-1-ol, and stir at 300 rpm for 10 h to obtain a mixture 2.
[0151] The mixture 2 was washed in a 0.12 mol / L KOH aqueous solution, and after adding 5-15 wt % of anhydrous copper sulfate desiccant, it was transferred to a vacuum environment and allowed to stand for 10 hours to obtain a mixture 3.
[0152] The mixture 3 was added to petroleum ether and recrystallized to obtain the final product, the compound N-((1,4-dioxane-2-yl)methyl)-2-(1-(trifluoromethyl)cyclohex-2-en-1-yl)acetamide described by formula (I-1).
[0153] TOF-MS(ESI)m / z calcd for C 14 H 20 F3NO4:323.13; [M+H] + found:323.63.
[0154]
[0155] Preparation of in-situ solid-state electrolyte:
[0156] 1. PC, DEC and EMC were mixed in a mass ratio of 2.5:3:5.5 and refrigerated at -15°C for 3 h to obtain a mixed solvent 1.
[0157] 2. 1 mol / L LiTFSi, 0.05 mol / L LiDFOB and 0.05 mol / L LiBOB were added to the mixed solvent 1 and stirred at 600 rpm for 4 h to obtain the basic electrolyte 1.
[0158] 3. 3 wt % FEC, 1.5 wt % DTD and 1 wt % PS were added to the basic electrolyte 1 in sequence, and the mixture was stirred at 800 rpm for 1 h to obtain the basic electrolyte 2.
[0159] 4. The compound N-((1,4-dioxane-2-yl)methyl)-2-(1-(trifluoromethyl)cyclohex-2-ene-1-yl)acetamide represented by formula (I-1), di(trimethylolpropane)tetraacrylate and methyl methacrylate were added to the electrolyte in a molar ratio of 8:1:1 and a total amount of 5wt%, and after stirring at a speed of 600 rpm for 1 hour, 0.1wt% of AIBN by weight of the polymerized monomer was added, and after stirring at a speed of 600 rpm for 2 hours, a mixed precursor 1 was obtained, which was an in-situ solid-state electrolyte.
[0160] Assembly of Lithium Metal Batteries:
[0161] 1. Disperse LCO (lithium cobalt oxide), conductive carbon superP, binder PVDF, and solid electrolyte LATP in NMP solvent (solid content 55%) at a mass ratio of 9.5:0.2:0.2:0.1, and stir in a homogenizer for 2 h to obtain a slurry.
[0162] 2. Apply the mixed slurry onto aluminum foil (coating surface density 12g / cm 2 ), dried in a vacuum oven at 80°C for 8 h, and then coated and rolled (compacted density 3.2 g / cm 3 ) to obtain the positive electrode.
[0163] 3. Transfer the dried positive electrode sheet to the glove box and punch it into a circular electrode sheet with a diameter of 12 mm.
[0164] 4. 2032 button cells were assembled in an argon-filled glove box (water and oxygen values were less than 0.1 ppm), the diaphragm was a polypropylene diaphragm coated with aluminum oxide on one side (the coating thickness of aluminum oxide was 2 μm, and the thickness of the polypropylene diaphragm was 9 μm), and the negative electrode was lithium metal. The amount of in-situ solid electrolyte added was 80 μL.
[0165] 5. Place the button cell in a 45°C oven for 24 h and charge the cell to 50% SOC at a rate of 0.2C to complete in-situ polymerization.
[0166] 6. The battery was cycled at a rate of 0.33C with a charge and discharge range of 3 to 4.6V. The results are shown in Table 1.
[0167] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 200 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3mm and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as shown below: Figure 1 shown.
[0168] Example 2
[0169] Synthesis of monomer: The synthesis process is the same as that of Example 1, except that the material 1-(trifluoromethyl)cyclohex-2-en-1-ol added in the monomer synthesis is replaced with 1-(trifluoromethyl)cyclopent-2-en-1-ol to obtain the compound represented by formula (I-2). TOF-MS (ESI) m / z calcd for C 13 H 18 F3NO4:309.12; [M+H] + found:309.44.
[0170]
[0171] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that in Example 1, except that the monomer added in step 4 is replaced by: the compound represented by formula (I-2), 1-(trifluoromethyl)cyclopent-2-en-1-yl((1,4-dioxane-2-yl)methyl)carbamate, bis(trimethylolpropane tetraacrylate), methyl methacrylate, in a molar ratio of 8:1:1, and the total amount added is 5wt%.
[0172] Assembly of lithium metal battery: Same as Example 1.
[0173] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3mm and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as follows Figure 2 shown.
[0174] Example 3
[0175] Synthesis of monomer: The synthesis process is the same as that of Example 1, except that the added material 1-(trifluoromethyl)cyclohex-2-en-1-ol is replaced with 1-(perfluoroethyl)cyclohex-2-en-1-ol to obtain the compound represented by formula (I-3). TOF-MS (ESI) m / zcalcd for C 15 H 20 F5NO4:373.13; [M+H] + found:373.22.
[0176]
[0177] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that of Example 1, except that the monomer added in step 4 is replaced by: the compound represented by formula (I-3) 1-(perfluoroethyl)cyclohex-2-en-1-yl((1,4-dioxane-2-yl)methyl)carbamate, bis(trimethylolpropane tetraacrylate) and methyl methacrylate, in a molar ratio of 8:1:1, and the total amount added is 5wt%.
[0178] Assembly of lithium metal battery: Same as Example 1.
[0179] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3mm and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as follows Figure 3 shown.
[0180] Example 4
[0181] Synthesis of monomer: The synthesis process is the same as that of Example 1, except that the material 1-(trifluoromethyl)cyclohex-2-ene-1-ol added in the monomer synthesis is replaced with 1,1,1-trifluoro-2-(trifluoromethyl)but-3-ene-2-ol to obtain the compound represented by formula (I-4). TOF-MS (ESI) m / z calcd for C 12 H 15 F6NO4:351.09; [M+H] + found:351.54.
[0182]
[0183] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that of Example 1, except that the monomer added in step 4 is replaced by: the compound represented by formula (I-4), 1,1,1-trifluoro-2-(trifluoromethyl)but-3-en-2-yl((1,4-dioxane-2-yl)methyl)carbamate, bis(trimethylolpropane tetraacrylate) and methyl methacrylate, in a molar ratio of 8:1:1, and the total amount added is 5wt%.
[0184] Assembly of lithium metal battery: Same as Example 1.
[0185] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3mm and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as follows Figure 4 shown.
[0186] Example 5
[0187] Synthesis of monomer: The synthesis process is the same as that of Example 1, except that the added material 1-(trifluoromethyl)cyclohex-2-ene-1-ol is replaced with 1,1,1-trifluoropent-4-ene-2-ol to obtain the compound represented by formula (I-5). TOF-MS (ESI) m / z calcdfor C 12 H 18 F3NO4:297.12; [M+H] + found:297.35.
[0188]
[0189] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that in Example 1, except that the monomer added in step 4 is replaced by: the compound represented by formula (I-5), 1,1,1-trifluoropent-4-en-2-yl((1,4-dioxane-2-yl)methyl)carbamate, bis(trimethylolpropane tetraacrylate) and methyl methacrylate, in a molar ratio of 8:1:1, and the total amount added is 5wt%.
[0190] Assembly of lithium metal battery: Same as Example 1.
[0191] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3m and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as follows Figure 5 shown.
[0192] Example 6
[0193] Synthesis of monomer: The synthesis process is the same as that of Example 1, except that the added material 1-(trifluoromethyl)cyclohex-2-ene-1-ol is replaced by: 4,4,5,5,5-pentafluoro-3-methylpent-1-ene-3-ol to obtain the compound represented by formula (I-6). TOF-MS (ESI) m / z calcd for C 11 H 13 F6NO4:337.07; [M+H] + found:337.43.
[0194]
[0195] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that in Example 1, except that the monomer added in step 4 is replaced by: the compound shown in formula (I-6) 3,4,4,5,5,5-hexafluoropent-1-en-3-yl((1,4-dioxane-2-yl)methyl)carbamate, bis(trimethylolpropane tetraacrylate) and methyl methacrylate, the molar ratio is 8:1:1, and the total amount added is 5wt%.
[0196] Assembly of lithium metal battery: Same as Example 1.
[0197] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3mm and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as follows Figure 6 shown.
[0198] Example 7
[0199] Synthesis of monomer: The synthesis process is the same as that of Example 1, except that the added material 1-(trifluoromethyl)cyclohex-2-en-1-ol is replaced by: 1,1,1,2,2-pentafluoro-3-(perfluoropropane-2-yl)hexyl-5-en-3-ol to obtain the compound represented by formula (I-7). TOF-MS (ESI) m / z calcd for C 15 H 15 F 12 NO4:501.08; [M+H] + found:501.22.
[0200]
[0201] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that of Example 1, except that the monomer added in step 4 is replaced by: the compound represented by formula (I-7), 1,1,1,2,2-pentafluoro-3-(perfluoropropane-2-yl)hexyl-5-en-3-yl((1,4-dioxane-2-yl)methyl)carbamate, bis(trimethylolpropane tetraacrylate) and methyl methacrylate, in a molar ratio of 8:1:1, and the total amount added is 5wt%.
[0202] Assembly of lithium metal battery: Same as Example 1.
[0203] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3mm and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as follows Figure 7 shown.
[0204] Comparative Example 1
[0205] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that of Example 1, except that the monomers added in step 4 are replaced by triethylene glycol dimethacrylate, di(trimethylolpropane tetraacrylate) and methyl methacrylate in a molar ratio of 8:1:1 and a total amount of 5wt%. At the same time, 0.1wt% of AIBN is added as an initiator.
[0206] Assembly of lithium metal battery: Same as Example 1.
[0207] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal negative electrode was removed. The lithium metal negative electrode was cut into small pieces of 3mm×3mm and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as follows Figure 8 shown.
[0208] Comparative Example 2
[0209] Preparation of in-situ solid-state electrolyte: The preparation process is the same as that of Example 1, except that the monomers added in step 4 are replaced by: methyl methacrylate, di(trimethylolpropane tetraacrylate) and methyl methacrylate, in a molar ratio of 8:1:1, and the total amount added is 5 wt%.
[0210] Assembly of lithium metal battery: Same as Example 1.
[0211] XPS test: In a glove box (water and oxygen ≤ 0.1ppm), the lithium metal battery with 100 cycles was disassembled and the lithium metal anode was removed. The lithium metal anode was cut into small pieces of 3mmx3m and bonded to the XPS test platform with conductive glue. The test was carried out and all test data were calibrated with C1s 284.8eV to obtain the XPS spectrum as shown below: Fig. 9 shown.
[0212] Table 1 Lithium metal battery cycle performance test results
[0213]
[0214] Since the new fluorine-containing polymer monomers are used in Examples 1 to 7, the end groups all contain strong electron-withdrawing groups, which are not easily oxidized by the ternary lithium positive electrode during the battery power cycle. At the same time, under the influence of the fluorine-containing group, the cyclic ether at the other end is more susceptible to the influence of the anion to polymerize. During the cycle, the monomer undergoes electropolymerization, which can reduce the amount of initiator used. At the same time, this type of monomer contains unsaturated double bonds, which can further ensure the sufficiency of monomer polymerization. Since the use of high-energy initiators is reduced, the side reactions of high-activity initiators with positive and negative electrodes are avoided, which is conducive to improving the cycle performance of the battery. At the same time, the monomer has the properties of some ether monomers, has good compatibility with lithium metal, and is conducive to forming a uniform and stable lithium fluoride SEI on the surface of the lithium metal negative electrode. It can be analyzed from the XPS energy spectrum that even after the cycle, there is still a strong lithium fluoride-rich peak on the surface of the lithium metal. The comparative example uses traditional acrylate monomers and azo initiators. Since the initiator with strong reaction activity will inevitably have a certain amount of residue, it is easy to have side reactions with the ternary lithium positive electrode and lithium metal, affecting the stability of the interface. At the same time, from the analysis of the XPS energy spectrum, it can be concluded that the lithium fluoride peak on the lithium metal surface of Comparative Examples 1 and 2 after cycling is significantly lower than the TFSI anion peak, reflecting the absence of a lithium fluoride interface. It is difficult to maintain a stable lithium fluoride SEI after polymerization of the acrylate monomer, and its interface stability is weaker than that of the embodiment.
[0215] From the cycle gram capacity and capacity retention rate, it can be concluded that the gram capacity and capacity retention rate of Examples 1 to 7 are higher than those of Comparative Example 1 and Comparative Example 2. This is because the same new polymer monomer is used in the examples to ensure good interface contact and stability, and at the same time, electropolymerization can be used to assist monomer polymerization, avoiding the use of high-energy initiators and reducing the occurrence of side reactions.
[0216] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An in-situ solid electrolyte for a high-voltage system, characterized in that: It is formed by polymerization of monomers and cross-linking agents in the electrolyte; The polymerizable monomers include a first monomer and a second monomer; The first monomer is as shown in formula (I) and / or formula (II); the second monomer is selected from acrylate monomers and / or amide monomers; Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles; n1 and n2 are each independently selected from integers of 1 to 5; R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group; R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group; The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group; The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group; R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
2. The in-situ solid electrolyte according to claim 1, characterized in that A in the formula (I) and the formula (II) is independently selected from one of the formulas (1) to (6):
3. The in-situ solid electrolyte according to claim 1, characterized in that The R is selected from one of the structures shown in formula (7) to formula (13): The R1 and R2 are each independently selected from the structure shown in formula (14) or formula (15):
4. The in-situ solid electrolyte according to claim 1, characterized in that The second monomer is selected from one or more of isobornyl methacrylate, isobornyl acrylate, N,N'-methylenebisacrylamide, methacrylamide, N-isopropylacrylamide, N-(3-dimethylaminopropyl)methacrylamide, N-vinylcaprolactam, methacrylamide, methacrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate and n-butyl acrylate; The crosslinking agent is selected from one or more of neopentyl glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, hexanediol diacrylate, di(trimethylolpropane tetraacrylate), pentaerythritol triacrylate, divinyl ether, trimethylolpropane triglycidyl ether, trivinyl cyanurate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, polyethylene glycol diacrylate and diallyl sulfide.
5. The in-situ solid electrolyte according to claim 1, characterized in that The molar ratio of the polymerizable monomer to the crosslinking agent is (5-15):1; The molar ratio of the first monomer to the second monomer is (5-9):(5-1); The total mass of the polymerized monomer and the cross-linking agent is 1% to 10% of the mass of the in-situ solid electrolyte.
6. The in-situ solid electrolyte according to claim 1, characterized in that The electrolyte includes an organic solvent, a lithium salt and an additive; The organic solvent includes a carbonate solvent; The concentration of the lithium salt in the electrolyte is 0.5 to 2 mol / L; The additive is selected from one or more of sulfonate compounds, sulfate compounds, fluorinated carbonate compounds, unsaturated cyclic carbonate compounds, borate compounds, trimethylsilyl ester compounds, nitrile compounds and fluorine-containing lithium salt compounds; the mass of the additive is 0.1% to 6% of the mass of the electrolyte.
7. A method for preparing an in-situ solid electrolyte for a high-voltage system, characterized in that: The following steps are involved: The polymerization monomer and the cross-linking agent are added to the electrolyte, and then the initiator is added in an amount of 0.1wt% to 1wt% of the polymerization monomer. After the reaction is continued, an in-situ solid electrolyte is obtained; The polymerizable monomers include a first monomer and a second monomer; The first monomer is as shown in formula (I) and / or formula (II); the second monomer is selected from acrylate monomers and / or amide monomers; Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles; n1 to n3 are each independently selected from integers of 1 to 5; R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group; R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group; The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group; The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group; R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
8. A lithium ion battery, characterized in that: It comprises the in-situ solid electrolyte for high-voltage system according to any one of claims 1 to 6 or the in-situ solid electrolyte for high-voltage system prepared by the preparation method according to claim 7.
9. A polyfluoro polymer monomer, characterized in that As shown in formula (I) or formula (II): Wherein, A in formula (I) and formula (II) is independently selected from substituted or unsubstituted oxygen-containing heterocycles; n1 to n3 are each independently selected from integers of 1 to 5; R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group; R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group; The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group; The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group; R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
10. A method for preparing a polyfluoropolymer monomer, characterized in that: The following steps are involved: In a protective atmosphere, the compound represented by formula (III) and the compound represented by formula (IV) or formula (V) are mixed in an organic solvent and reacted under low temperature conditions to obtain a polyfluoro polymer monomer; R-OH formula (IV); A is selected from a substituted or unsubstituted oxygen-containing heterocycle; n1 and n2 are each independently selected from integers of 1 to 5; R is selected from a substituted unsaturated carbocyclic ring containing a carbon-carbon double bond or a substituted C2-C20 alkenyl group; R1 and R2 are each independently selected from a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a substituted C2-C20 alkenyl group or a C1-C10 perfluoroalkyl group; The substituent in the substituted C2-C20 alkenyl group is selected from one or more of a substituted or unsubstituted unsaturated carbocyclic ring containing a carbon-carbon double bond, a C1-C5 alkyl group, and a C1-C5 perfluoroalkyl group; The substituents in the substituted nitrogen-containing heterocycle and the substituted unsaturated carbon ring containing a carbon-carbon double bond are each independently selected from a C1-C5 alkyl group and / or a C1-C5 perfluoroalkyl group; R contains a perfluoroalkyl group, and at least one of R1 and R2 contains a perfluoroalkyl group and at least one of them contains a carbon-carbon double bond.
Citation Information
Patent Citations
Polymer electrolytes for in situ polymerization of lithium ion batteries
CN114207894A
Double-coating diaphragm capable of simultaneously inhibiting dissolution of lithium dendrites and transition metals, preparation method and lithium metal battery applying diaphragm
CN115133222A
